Superhydrophobicity of microstructured surfaces on zirconia by nanosecond pulsed laser. Issue 1 (May 2019) - Cai, Yukui; Chang, Wenlong; Luo, Xichun; Qin, Yi
Abstract: This article presents a systematic approach to improve the hydrophobicity of microstructured surfaces. It includes a contact angle prediction model for microstructures obtained by nanosecond pulsed laser. Combining with the theoretical constraints for stable Cassie–Baxter state, this approach can be used to optimize microstructures dimensions for maximizing surface hydrophobicity. Laser machining experiments were conducted to evaluate the prediction model. It shows that the proposed systematic approach can accurately predict the contact angle and obtain microstructures dimensions for maximizing surface hydrophobicity. The results also indicate that the contact angle increases with the decrease of pitch of the microstructures. Superhydrophobicity with maximum contact angle of 155.7° is obtained, for the first time, on a microstructured surface (P030) of zirconia with a pitch of 30 µm machined under a laser power at 8W.